RADT-31. TREATMENT TRENDS AND SURVIVAL OUTCOMES IN ATYPICAL MENINGIOMA. (12th November 2021) - Syed, Yusef; Rupji, Manali; Switchenko, Jeffrey; Eaton, Bree; Olson, Jeffrey; Kimberly, Hoang; Bray, David; Shu, Hiu-Kuo; Zhong, Jim
Abstract: BACKGROUND: WHO grade II (atypical) meningiomas are treated with surgical resection, often followed by adjuvant fractionated radiation therapy (FRT). The increased availability of frameless stereotactic radiosurgery (SRS) presents an opportunity to offer patients a high biological effective dose over fewer fractions. Here we study the patterns of care and outcomes of these two forms of adjuvant RT. METHODS: Patients with atypical meningioma were abstracted from the National Cancer Database (NCDB). Descriptive statistics were reported, and differences between treatment groups were assessed using either a chi-square test or ANOVA. Patients were grouped by treatment type and Kaplan Meier (KM) analysis was performed to compare overall survival (OS) using a log rank test. Univariable (UVA) and multivariable (MVA) cox regression analyses were completed. RESULTS: Of 10, 015 cases diagnosed from 2004-2016, 7, 153 received surgery alone, 2, 059 received surgery and adjuvant FRT (S+RT), and 362 received adjuvant SRS (S+SRS). The use of adjuvant RT increased by 71.8% for S+RT and 97.8% for S+SRS. In 2004, 15.1% of 443 registered patients received S+RT and 2.26% received S+SRS, while in 2016 these figures were 26.0% and 4.47%, respectively, for the 1051 registered patients (p< 0.001 and 0.022, respectively). For the 8, 636 patients with survival data there was no significant difference in median OS between S+RT and S+SRS (130 months vs. 125 months, log rank p=0.935). On UVA, S+RT conferred better survival compared to surgery alone (HR 0.81 [0.72-0.91], p< 0.001) while S+SRS trended towards better survival (HR 0.82 [0.64-1.06], p=0.124). On MVA, no significant OS benefit was seen with S+RT (HR 0.96 [0.85-1.08], p=0.491) or S+SRS (HR 0.90 [0.69-1.16], p=0.413) versus surgery alone. CONCLUSIONS: While the use of adjuvant RT for atypical meningioma has increased substantially since 2004, OS is comparable between FRT and SRS. The data presented here support further prospective investigation of adjuvant SRS.